2010
DOI: 10.1002/gcc.20798
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome band 17q21 in breast cancer: Significant association between beclin 1 loss and HER2/NEU amplification

Abstract: Treatment success of breast cancer patients with trastuzumab alone or in combination depends not only on HER2/NEU amplification but also on PTEN and PI3K status and efficient cell death programs. In this pilot study, we found a significant association between loss of beclin 1 and HER2/NEU amplification (both on 17q21) in breast cancers. This finding was confirmed in two public copy number microarray datasets. Furthermore, there is a trend associating beclin 1 loss with TP53 mutations, PI3KCA gene gain, and PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…Given the prevalence of resistance in ER + breast cancers, autophagy inhibition might serve as an advantageous combination strategy for these subsets of breast cancer patients. Similarly, in a small cohort of breast cancer patients with HER2/c-neu amplification, the concomitant loss of Beclin-1 is significantly associated with better clinical response to trastuzimab, indicative of the cell deathpromoting aspect of autophagy in response to the targeted treatment [76]. This evidence supports the hypothesis that defective autophagy functions as a modifier, potentially a fundamental driver, of genomic damage during tumor progression.…”
Section: Autophagy Inhibitionsupporting
confidence: 71%
See 1 more Smart Citation
“…Given the prevalence of resistance in ER + breast cancers, autophagy inhibition might serve as an advantageous combination strategy for these subsets of breast cancer patients. Similarly, in a small cohort of breast cancer patients with HER2/c-neu amplification, the concomitant loss of Beclin-1 is significantly associated with better clinical response to trastuzimab, indicative of the cell deathpromoting aspect of autophagy in response to the targeted treatment [76]. This evidence supports the hypothesis that defective autophagy functions as a modifier, potentially a fundamental driver, of genomic damage during tumor progression.…”
Section: Autophagy Inhibitionsupporting
confidence: 71%
“…On the other hand, overexpression of Beclin-1 leads to a decrease in MCF-7 cellular proliferation, and breast cancer formation occurs in nude mice. Furthermore, Negri et al [76] reported that Becn1 heterozygosity suppressed Palb2-associated mammary tumorigenesis by p53-dependent mechanism in Palb2 f/f ;Wap-Cre;Becn1 +/− mice.…”
Section: Beclin-1mentioning
confidence: 99%
“…Importantly, some of these abnormalities have been shown to correlate with clinicopathological parameters and disease outcomes including overall survival in cancer patients. These findings not only underscore a pivotal role of autophagy in tumorigenesis, but also highlight the possibility of using autophagy-associated molecules as novel prognostic markers in clinical settings (Russell et al, 1990;Eccles et al, 1992;Futreal et al, 1992;Cliby et al, 1993;Saito et al, 1993;Gao et al, 1995;Ahn et al, 2007;Miracco et al, 2007Miracco et al, , 2010Ding et al, 2008;Fujii et al, 2008;Yoshioka et al, 2008;Kim et al, 2008a;Kang et al, 2009;Lazova and Pawelek, 2009;Nomura et al, 2009;Othman et al, 2009;Pirtoli et al, 2009;Li et al, 2009Zhang et al, 2009a;Koukourakis et al, 2010;Lazova et al, 2010;Miao et al, 2010;Negri et al, 2010;Sivridis et al, 2010;Wan et al, 2010;Karpathiou et al, 2010;Chang et al, 2011;Ma et al, 2011).…”
Section: Dysregulation Of Autophagy In Human Cancersmentioning
confidence: 88%
“…[22][23][24] Accordingly, a significant association between loss of beclin 1 and amplification of the HER2/ NEU oncogene was described in breast carcinoma. 25 Quenching ROS with N-acetyl l-cysteine (NAC) delayed the promotion of aneuploidy and improved survival of beclin 1 þ / À cells, revealing that ROS contributes to genomic instability in these cells. 23,24 Interestingly, expression of p62 increased ROS and DNA damage in autophagy-defective cells under metabolic stress, thereby revealing that p62 accumulation may potentiate generation of ROS due to dysfunctional mitochondria.…”
Section: Autophagy Mitochondria Metabolism and Tumorigenesismentioning
confidence: 99%